AUSTRALIA’S PARTICIPATION AND PERFORMANCE AT THE EVIAN CONFERENCE: INTEGRITY OR SHAME? - P. R. Bartrop (Vestnik MGIMO-Universiteta, 2018)
This article outlines and assesses the contribution made by the Commonwealth of Australia to the Evian Conference of July 1938. The attitude of the Australian government, it will be shown, was ambivalent from the start, with the Commonwealth not even prepared to attend unless Britain also attended. Having then made the commitment to send a representative to Evian, the Australian government chose a man who was neither an immigration expert nor a man with any foreign affairs expertise. Thomas (later Sir Thomas) White, the Australian Minister for Trade and Customs, was a senior minister in the Cabinet of Prime Minister Joseph Lyons, but the experience required for the task of representing Australia at a gathering such as Evian was simply beyond him. The legalistic and unsympathetic stance he adopted led to despair for many of the Jewish delegates at Evian. Upon elected to the chairmanship of one of the two subcommittees set up at the conference, White employed his position to treat the Jewish delegates with utter contempt. His record at the conference, lauded by many of the officials who were present, was one of the least humanitarian of any that can be attributed to Australian statesmen—hardly a ringing endorsement of Australia’s record at this crucial gathering in which the Commonwealth sought, at an early stage, to express itself as an autonomous nation on the international stage.